Analisis Implementasi Penggunaan Aplikasi Primary Care Dalam Menunjang Efektivitas Pelayanan Rawat Jalan di UPTD Puskesmas Rawat Inap Ciranjang - Sri Dewi Wahyuni; Irda Sari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
UPTD Ciranjang Inpatient Health Center is a health facility that has been using the Primary Care (PCare) application since 2014. However, from the beginning of its implementation until now, PCare often encounters obstacles for its users, one of which is often experiencing errors that can interfere with the service process at the Puskesmas, especially in outpatient units. The purpose of this study is to determine the implementation of the use of the Primary Care application in supporting the effectiveness of outpatient services at UPTD Ciranjang Inpatient Health Center. This type of research is descriptive qualitative research with a case study approach. This research was conducted at UPTD Ciranjang Inpatient Health Center from March to May 2023. Data collection was obtained through observation, in-depth interviews with PCare operators, and documentation. The results showed that in the implementation of the PCare application at UPTD Ciranjang Inpatient Health Center, several obstacles were still found, including the performance of the PCare application which often experienced errors, inaccurate patient data accuracy and slow communication with BPJS, the number of human resources that were still lacking, supporting facilities and infrastructure were still not met, and application integration was not optimal.